2022
DOI: 10.2174/1871520622666220418131935
|View full text |Cite
|
Sign up to set email alerts
|

CDC25B Inhibition by Menadione: A Potential New Therapeutical Approach

Abstract: Gastric cancer (GC) is the fifth most common type of tumor and the third leading cause of cancer death worldwide. The evolution of gastric carcinogenesis is still poorly understood and, for this reason, preclinical research protocols were established that included the development of gastric cancer cell lines and the establishment of models of gastric carcinogenesis in non-human primate Sapajus apella. A comprehensive literature search was performed in relevant databases such as PubMed, ResearchGate and Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…The findings reported in this study show that naphthoquinones could be a group of compounds with specific allosteric inhibitory effects on the Mycobacterium tuberculosis protein tyrosine phosphatase A. Ribiero et al [ 50 ] reviewed the potential for developing CDC25 inhibition via the naphthoquinone menadione for therapeutic applications. Yoshikawa et al [ 51 ] showed that menadione inhibits another PTP, PTEN, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The findings reported in this study show that naphthoquinones could be a group of compounds with specific allosteric inhibitory effects on the Mycobacterium tuberculosis protein tyrosine phosphatase A. Ribiero et al [ 50 ] reviewed the potential for developing CDC25 inhibition via the naphthoquinone menadione for therapeutic applications. Yoshikawa et al [ 51 ] showed that menadione inhibits another PTP, PTEN, both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 83%
“…The estimated IC 50 values are shown in Table 1. Among these, shikonin showed strong inhibition (IC 50 33 µM) at a concentration that is potentially clinically relevant. This is consistent with reports in the literature of the inhibition of other protein tyrosine phosphatases via shikonin.…”
Section: Inhibition Of Mt-ptpa By Epigallocatechin Myricetin Rosmarin...mentioning
confidence: 99%